Body Temperature Enhanced Adhesive, Antibacterial, and Recyclable Ionic Hydrogel for Epidermal Electrophysiological Monitoring (Adv. Healthcare Mater. 15/2022). Issue 15 (3rd August 2022) - Liu, Ying; Wang, Chan; Xue, Jiangtao; Huang, Guanhua; Zheng, Shuang; Zhao, Ke; Huang, Jing; Wang, Yiqian; Zhang, Yan; Yin, Tailang; Li, Zhou
Abstract : Electrophysiological Monitoring A multifunctional ionic hydrogel based on dual physical cross‐linked networks helps build a highly compliant and gapless interface with the skin, as described by Tailang Yin, Zhou Li, and co‐workers in article number 2200653 . When applied as the epidermal electrode, it shows good capability to record multifarious electrophysiological signals with high signal‐to‐noise ratio and ultra‐low detection limit.